Making architecture through being human : a handbook of design ideas - Plowright, Philip D. (New York Routledge, 2020)
"Architecture can seem complicated, mysterious or even ill-defined, especially to a student being introduced to architectural ideas for the first time. One way to approach architecture is simply as the design of human environments. When we consider architecture in this way, there is a good place to start - ourselves. Our engagement in our environment has shaped the way we think which we, in turn, use to then shape that environment. It is from this foundation that we produce meaning, make sense of our surroundings, structure relationships and even frame more complex and abstract ideas. This is the start of architectural design. Making Architecture Through Being Human is a reference book that presents 52 concepts, notions, ideas and actions that are fundamental to human thinking and how we interpret the environment around us. The book focuses on the application of these ideas by architectural designers to produce meaningful spaces that make sense to people. Each idea is isolated for clarity in the manner of a dictionary with short and concise definitions, examples and illustrations. They are organized in five sections of increasing complexity or changing focus. While many of the entries might be familiar to the reader, they are presented here as instances of a larger system of human thinking rather than simply graphic or formal principles. The cognitive approach to these design ideas allows a designer to understand the greater context and application when aligned with their own purpose or intentions"--
Keywords: Architectural design; Architecture -- Human factors